Transferring power and data simultaneously of different direction in ultrasonic contactless power transfer system - Maopeng Wu; Lijuan Su; Xiyou Chen; Xiaoli Duan; Donghua Wu; Yu Jiang (Energy Reports, 2022)
Ultrasonic contactless power transfer (UCPT) technology is a new kind of contactless power transfer (CPT) technology, which can be used to transfer power to loads in enclosed metal containers. In this paper, an UCPT system of transferring power and data simultaneously of different direction using only one pair of transducer is proposed. In the proposed system, power is transferred from the transmitting side to receiving side, and data is transferred in reverse direction simultaneously, from receiving side to transmitting side. The proposed system consists of power transfer channel and data backward transfer channel. The power transfer channel is modeled and the data backward transfer channel is analyzed in detail. 2ASK technology is used in data transfer channel. To show the effectiveness of the proposed system, an experimental setup is built. For power transfer channel, the output power is up to 40 W, and for data transfer channel, the data transfer rate is up to 1.6 kbps in ideal situation. When transferring a picture, the data transfer rate is 1.43 kbps and the output voltage is 5V which are realized at the same time.